SAURON observations of sa bulges: The formation of a kinematically decoupled core in NGC 5953 - Falcon-Barroso, J; Bacon, R; Bureau, M; Cappellari, M; Davies, R; de Zeeuw, P; Emsellem, E; Fathi, K; Krajnovic, D; Kuntschner, H; McDermid, R; Peletier, R; et al. (2007)
We present results from our ongoing effort to understand the nature and evolution of nearby galaxies using the SAURON integral-field spectrograph. In this proceeding we focus on the study of the particular case formed by the interacting galaxies NGC 5953 and NGC 5954. We present stellar and gas kinematics of the central regions of NGC5953. We use a simple procedure to determine the age of the stellar populations in the central regions and argue that we may be witnessing the formation of a kinematically decoupled component (hereafter KDC) from cold gas being acquired during the ongoing interaction with NGC 5954.